Maquinaria Agrícola en la explotación del cultivo de tabaco (Nicotiana tabacum) en el Ecuador - Navarrete Rodríguez, Franklin Aldair (2024)
In the development of this research based on the "Agricultural Machinery in the exploitation of tobacco cultivation (Nicotiana tabacum) in Ecuador. In which it was raised as an objective, was to describe the impact of mechanized tillage on the productivity of tobacco cultivation (Nicotiana tabacum) in Ecuador. The methodology, it is determined that it was based on a basic type of research, where it was developed under a descriptive-analytical approach, with a qualitative research design, in its development the origin of tobacco, its botanical characteristics, economic importance and geographical location, tillage, types of tillage and components of mechanized tillage. Regarding the results, an average saving of 30% in labor costs was obtained. However, the large investment necessary for the acquisition of agricultural machinery must be compared with this initial saving, in addition, a more vigorous and uniform growth of the plants is favored by the improvement in the structure of the soil. In conclusion, with an average increase of 25% in yields per hectare, the use of mechanized tillage has significantly improved the productivity of tobacco crops in Ecuador. In addition, maintaining humidity, essential for the development of tobacco, and preserving soil structure are benefits of these techniques. Also, the uniformity and precision of the machinery allow for a more homogeneous plantation and better control of soil conditions, which can result in higher productivity.